Osteocyte Estrogen Receptor β (Ot‐ERβ) Regulates Bone Turnover and Skeletal Adaptive Response to Mechanical Loading Differently in Male and Female Growing and Adult Mice. (19th December 2022) - Xu, Xiaoyu; Yang, Haisheng; Bullock, Whitney A.; Gallant, Maxim A.; Ohlsson, Claes; Bellido, Teresita M.; Main, Russell P.
ABSTRACT: Age‐related bone loss is a failure of balanced bone turnover and diminished skeletal mechanoadaptation. Estrogen receptors, ERα and ERβ, play critical roles in osteoprotective regulation activated by estrogen and mechanical signals. Previous studies mainly focused on ERα and showed that osteocyte‐ERα (Ot‐ERα) regulated trabecular, but not cortical bone, and played a minor role in load‐induced cortical adaptation. However, the role of Ot‐ERβ in bone mass regulation remains unrevealed. To address this issue, we characterized bone (re)modeling and gene expression in male and female mice with Ot‐ERβ deletion (ERβ‐dOT) and littermate control (LC) at 10 weeks (young) or 28 weeks (adult) of age, as well as their responses to in vivo tibial compressive loading. Increased cancellous bone mass appeared in the L4 vertebral body of young male ERβ‐dOT mice. At the same time, femoral cortical bone gene expression showed signs consistent with elevated osteoblast and osteoclast activities (type‐I collagen, Cat K, RANKL). Upregulated androgen receptor (AR) expression was observed in young male ERβ‐dOT mice relative to LC, suggesting a compensatory effect of testosterone on male bone protection. In contrast, bone mass in L4 decreased in adult male ERβ‐dOT mice, attributed to potentially increased bone resorption activity (Cat K) with no change in bone formation. There was no effect of ERβ‐dOT on bone mass or gene expression in female mice. Sex‐dependent regulation of Ot‐ERβ also appeared in load‐induced cortical responsiveness. Young female ERβ‐dOT mice showed an enhanced tibial cortical anabolic adaptation compared with LC. In contrast, an attenuated cortical anabolic response presented at the proximal tibia in male ERβ‐dOT mice at both ages. For the first time, our findings suggest that Ot‐ERβ regulates bone (re)modeling and the response to mechanical signals through different mechanisms in males and females. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).